Applying Landscape Ecological Metrics on Land Use Change in Lanyang Plain - Hsiao-Wen Wang (European Regional Science Association (ERSA), 2005)
Land use is the human activity affecting by economical, cultural, political and historical factors and presents complex, uncertainty and spatiotemporal characteristics. Understanding of land use change and its trend are necessary for understanding the environmental problems. Nestled between the Pacific Ocean in the east and the Central and Snow Mountains in the north and southwest, Lanyang Plain is one of Taiwans most picturesque and secluded geographical areas. However, due to the great construction, Taipei-Yilan highway, the regional landscape structure on a large scale in this area has been directly changed. The original ecological function was thus deteriorated a lot. Conflicts between ecological and socio-economic aspects tend to obstruct the implementation of traditional landscape policy instruments. In this study, land use data in 1982, 1984, 1994, and 2002 surveyed by the government were collected to analyze land use change. After classifying land use categories from the original data, landscape structure in landscape and class scale levels are quantified by calculating landscape metrics. The quantified indices as well as the related events and their driving forces are discussed further. Proper mitigation strategies are then proposed as the suggestions for future management.
Keywords: 330